Idiopathic Intracranial Hypertension in the United States: Demographic and Socioeconomic Disparities - Ghaffari-Rafi, Arash; Mehdizadeh, Rana; Ko, Andrew Wai Kei; Ghaffari-Rafi, Shadeh; Leon-Rojas, Jose (Frontiers in Neurology, 2020)
Background: Obesity's risk increases for low-income, female, young, and Black patients. By extrapolation, idiopathic intracranial hypertension (IIH)—a disease associated with body mass index—would potentially display socioeconomic and demographic disparities. Methods: IIH incidence (per 100,000) was investigated with respect to sex, age, income, residence, and race/ethnicity, by querying the largest United States (US) healthcare administrative dataset (1997–2016), the National (Nationwide) Inpatient Sample. Results: Annual national incidence (with 25th and 75th quartiles) for IIH was 1.15 (0.91, 1.44). Females had an incidence of 1.97 (1.48, 2.48), larger (p = 0.0000038) than males at 0.36 (0.26, 0.38). Regarding age, largest incidence was among those 18–44 years old at 2.47 (1.84, 2.73). Low-income patients had an incidence of 1.56 (1.47, 1.82), larger (p = 0.00024) than the 1.21 (1.01, 1.36) of the middle/high. No differences (χ2 = 4.67, p = 0.097) were appreciated between urban (1.44; 1.40, 1.61), suburban (1.30; 1.09, 1.40), or rural (1.46; 1.40, 1.48) communities. For race/ethnicity (χ2 = 57, p = 2.57 × 10−12), incidence was largest for Blacks (2.05; 1.76, 2.74), followed by Whites (1.04; 0.79, 1.41), Hispanics (0.67; 0.57, 0.94), and Asian/Pacific Islanders (0.16; 0.11, 0.19). Year-to-year, incidence rose for all strata subsets except Asian/Pacific Islanders (τ = −0.84, p = 0.00000068). Conclusion: IIH demonstrates several sociodemographic disparities. Specifically, incidences are larger for those low-income, Black, 18–44 years old, or female, while annually increasing for all subsets, except Asian/Pacific Islanders. Hence, IIH differentially afflicts the US population, yielding in healthcare inequalities.